2022
DOI: 10.51620/0869-2084-2022-67-3-170-176
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of causative agents of transmissive tick-borned ricketsious in the Crimean peninsula

Abstract: The paper presents the results of a study of the prevalence of Ixodid ticks - potential carriers of tick-borne rickettsiosis pathogens. Ectoparasites were collected in various natural and climatic zones of the Crimean Peninsula within the year 2016-2018. As a result of screening with the help of real-time PCR analysis (PCR-RT), a genetic marker (a section of the gltA gene) of the rickettsia group of tick-borne spotted fever was detected in ticks. The most common DNA marker of rickettsia was found in ticks in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…On day 2 of treatment (July 25) a scab was removed from the eschar and the underlying area was sampled using a dry sterile cotton swab by gentle rotation in the wound area and transferred into a sterile container containing 200 µL of sterile PBS and stored at −20 °C. Two separate DNA extractions were performed each using 100 µL of swab material using “Real Best Extraction 100” reagent kit according to the manufacturer's instructions (“Vector-Best”, Novosibirsk), purified DNA was eluted using 100 µL of the elution buffer as described previously [11 , 12] . Each DNA was first tested in triplicates for Rickettsia glt A fragment using “Real Best DNA Rickettsia species” reagent kit (“Vector-Best”) and corresponding positive and negative controls included with the kit.…”
Section: Laboratory Investigation and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On day 2 of treatment (July 25) a scab was removed from the eschar and the underlying area was sampled using a dry sterile cotton swab by gentle rotation in the wound area and transferred into a sterile container containing 200 µL of sterile PBS and stored at −20 °C. Two separate DNA extractions were performed each using 100 µL of swab material using “Real Best Extraction 100” reagent kit according to the manufacturer's instructions (“Vector-Best”, Novosibirsk), purified DNA was eluted using 100 µL of the elution buffer as described previously [11 , 12] . Each DNA was first tested in triplicates for Rickettsia glt A fragment using “Real Best DNA Rickettsia species” reagent kit (“Vector-Best”) and corresponding positive and negative controls included with the kit.…”
Section: Laboratory Investigation and Resultsmentioning
confidence: 99%
“…Each DNA was first tested in triplicates for Rickettsia glt A fragment using “Real Best DNA Rickettsia species” reagent kit (“Vector-Best”) and corresponding positive and negative controls included with the kit. Amplification and sequencing larger portions of Rickettsia glt A, omp A, omp B and sca 4 was done according to the previously described protocols [11 , 12] . Primers used are listed in Supplementary Table S1.…”
Section: Laboratory Investigation and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contemporary acarological studies conducted in the Crimea Peninsula during the last decade indicated the occurrence of diverse tick species in different ecological settings [ 92 , 93 , 94 ]. Nidicolous R. sanguineus is mostly present in the peridomestic environment [ 75 , 76 ].…”
Section: Contemporary Tick Surveillance Efforts In Countries Adjacent...mentioning
confidence: 99%